2020
DOI: 10.4103/jehp.jehp_768_19
|View full text |Cite
|
Sign up to set email alerts
|

The effect of educational intervention on health-promoting lifestyle: Intervention mapping approach

Abstract: BACKGROUND: The health-promoting lifestyle by empowering individuals will increase control over their health, improve quality of life, and prevent diseases. The purpose of the present study was to determine the effect of the educational intervention based on the intervention mapping approach on health-promoting lifestyle in Iranian college students. METHODS: This study is a quasi-experimental control study that was conducted in two groups of 65 students of Iran Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Chronic diseases are often caused by unhealthy living conditions (Solhi et al. , 2020 ). This study showed that women with chronic diseases used more health services.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic diseases are often caused by unhealthy living conditions (Solhi et al. , 2020 ). This study showed that women with chronic diseases used more health services.…”
Section: Discussionmentioning
confidence: 99%
“…Meetings of international project coordinators, such as Erasmus is also a good place to discuss health in a cultural context. Research shows that planned health education among students, promoting a healthy lifestyle in various dimensions, improves pro-health attitudes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patterns of health behaviour choices are governed by many factors (e.g., habits, the influence of family and peers, age, gender, place of residence, education level, socio-economic status, mental state, and psychological characteristics of an individual) [3] (pp. [46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Health education aims to encourage patients to actively learn new methods for achieving the purposes of preventing diseases, improve health status and increase the life quality. [7,8] Medical-nurse integration health education has become increasingly important in recent years due to the benefits it provides for patients in terms of improving their health and well-being. It helps patients better understand their health conditions, treatment options, and how to manage their symptoms, leading to improving patient outcomes, such as reduced hospital readmissions and improved quality of life.…”
Section: Introductionmentioning
confidence: 99%